Population pharmacokinetics of vancomycin in Thai patients - Tunggul Adi Purwonugroho (2018)
Population pharmacokinetics of vancomycin in Thai adult patients was determined by non-linear mixed-effects approach using 319 vancomycin serum concentrations from 212 patients. The data were best fitted by a two-compartment model and it was used to examine the effect of patient characteristics on the vancomycin pharmacokinetics. In the final model, there was a linear relationship between vancomycin clearance, CL (L/h), and creatinine clearance calculated by Cockcroft-Gault equation, CLCr (mL/min): CL=0.044 × CLCr. Meanwhile, volume of central compartment, V 1 (L), was linearly related with the age (years old): V 1 =0.542 × Age. Intercompartment clearance (Q) and volume of peripheral compartment (V 2) was 6.95L/h and 44.2L, respectively. The interindividual variability for CL, V 1, Q, and V 2 was 35.78, 20.93, 39.50, and 57.27%, respectively. Whereas, the intraindividual variability was 4.51mg/L. Final model then was applied to predict serum vancomycin concentrations on validation group. Predictive performance revealed a bias of -1.43mg/L (95% CI: -5.82-2.99) and a precision of 12.2mg/L (95% CI: -1.60-26.16). In conclusion, population pharmacokinetic of vancomycin in Thai adult patients was developed. The model could be used to create vancomycin dosage regimen in the type of patient similar with the present study. Copyright 2012 Tunggul Adi Purwonugroho et al.